Unraveling The Impact of Feed Protein Content on Catfish (Clarias sp.) Growth, Survival, Meat Quality and Gastrointestinal Histology - Septriani, Nur Indah; Nizma, Nata Dwi Annisa; Paramita, Pradnya (Biota, 2024)
Catfish is a highly favored source of protein in Indonesia. Catfish farming can be carried out using various types of feed and methods. This research aims to determine the effect of two types of fish feed with high (24%) and low (4%) protein content on several aspects of catfish cultivated using the pond/bucket culture method. The methods include catfish maintenance, physicochemical measurement, morphometric measurements, survival rate measurements, proximate testing, and histological preparations of catfish intestines and stomach. The results show that the TDS and pH values in the high-protein feed are higher than in the low-protein feed, while the temperature fluctuates. At the end of the observation, there is a significant difference in the morphometry of catfish fed with high-protein feed, where the body weight, head width, and body length are higher. The difference in body weight of catfish fed with high-protein feed is significantly higher (119.58±16.72 g) compared to those fed with low-protein feed (52.20±4.80 g). The average number of surviving catfish fed with high-protein feed is lower (27.60±8.23 fish) compared to the other group (44.00±2.55 fish). Proximate testing indicates that catfish meat with high-protein feed also has higher protein, fat, and carbohydrate content. Histological analysis shows that catfish with high-protein feed have longer villi and higher number of goblet cells, while the length of the gastric pits is lower. This research demonstrates that high-protein feed has an impact on fish quality, while ensuring water quality to reduce catfish mortality rates in catfish pond culture.